Variations in active layer soil hydrothermal dynamics of typical wetlands in permafrost region in the Great Hing’an Mountains, northeast China - Xingfeng Dong (Elsevier, 2021)
The freeze–thaw process of active layer can alter soil hydrothermal dynamics and plays an important role in the stability of permafrost ecosystem, particularly under the background of permafrost degradation resulting from climate warming. Wetlands in permafrost regions are considered to be symbiotic with permafrost. However, despite being the principal region of high-latitude permafrost in China, research on the freeze–thaw process in wetland in the Great Hing’an Mountains is limited. In this study, soil temperature and moisture data (from September 2018 to August 2020) collected from shrub and forest swamp observational sites in the Great Hing’an Mountains were used to analyze the freeze–thaw process and soil hydrothermal dynamics. The effect of wetland types on the freeze–thaw process and the coupling characteristics of soil temperature and moisture were discussed. The results demonstrated that the thawing process of active layer was unidirectional, while the freezing was bidirectional, and the thawing process took much longer than freezing process. The distribution of temperature and moisture of active layer varied in different stage of freeze–thaw process, yet similar trends were exhibited in different wetland types during the same freeze–thaw stage. The annual average temperature of forest swamp was higher than that of shrub swamp for all soil depths, while the annual average water content of forest swamp was lower than that of shrub swamp. A significant non-linear correlation was observed between moisture and temperature of each soil layer.